Validación piloto de la batería psicopedagógica evalúa-0 (2019)
The purpose of this project was the pilot validation of the Evaluacion-0 Psychopedagogical Battery. Which has a curricular nature and is designed to provide relevant data in the assessment of cognitive, spatial, linguistic and adaptation skills in children who complete transition and begin the first cycle of primary education, allowing the taking of decisions about educational processes in terms of possible curricular adaptations that best fit the needs of students. This research is framed within the analytical empirical paradigm, instrumental study, and a descriptive scope; Initially, the analysis of the levels of internal consistency between the 10 expert judges was carried out and the suggested modifications were made to the instrument Evaluates-0. Subsequently, the pilot application of the test was carried out to 84 participants whose ages ranged from 5 to 6 years. Among the instruments used for data collection are: (a) Psychopedagogical Battery Evaluates-0 (a =, 928); (b) Child Neuropsychological Evaluation ENI-2 (a =, 641); (c) Questionnaire for parents (a =, 706); (d) Clinical history (a =, 102). The results indicate an adequate level of validity contained with a Cronbach's alpha (a =, 886) with a high internal consistency for the items with a Cronbach's alpha of (a =, 928). The convergent validity checks the correlations between the subtests of the instruments. Which concludes that Evalúa-0 has excellent psychometric properties which makes it an ideal tool for psychopedagogical evaluations of Colombian institutions.